2021
DOI: 10.1177/0271678x211045748
|View full text |Cite
|
Sign up to set email alerts
|

A new perspective on cerebrospinal fluid dynamics after subarachnoid hemorrhage: From normal physiology to pathophysiological changes

Abstract: Knowledge about the dynamic metabolism and function of cerebrospinal fluid (CSF) physiology has rapidly progressed in recent decades. It has traditionally been suggested that CSF is produced by the choroid plexus and drains to the arachnoid villi. However, recent findings have revealed that the brain parenchyma produces a large portion of CSF and drains through the perivascular glymphatic system and meningeal lymphatic vessels into the blood. The primary function of CSF is not limited to maintaining physiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 145 publications
(309 reference statements)
0
18
0
Order By: Relevance
“…However, only few of the seven patients underwent CSF test during follow‐up period. Lumbar punctures were done due to theories that CSF circulation plays an important role during the brain repair process 33,34 . However, studies with a large number of cases are still ongoing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only few of the seven patients underwent CSF test during follow‐up period. Lumbar punctures were done due to theories that CSF circulation plays an important role during the brain repair process 33,34 . However, studies with a large number of cases are still ongoing.…”
Section: Discussionmentioning
confidence: 99%
“…Lumbar punctures were done due to theories that CSF circulation plays an important role during the brain repair process. 33 , 34 However, studies with a large number of cases are still ongoing. Endovascular stenting may be a safe and effective way to improve IJV stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…The balance between CSF pressure and precapillary and venous pressure is unbalanced in favour of higher CSF, and the volume of fluid in the brain is further increased. 66 In addition, hindrance of CSF circulation along glymphatic pathways is another mechanism that may interrupt the drainage of damaging substances from the subarachnoid space and parenchyma 23 because a recent finding of CSF flow block did not correlate with the size of haemorrhage, 67 while CSF macrophage CD163, a haemoglobin scavenger receptor for blood clearance, was significantly associated with hydrocephalus and outcome after SAH in patients. 68 Moreover, meningeal lymphatics also participate in clearing red blood cells from the CSF to cervical lymph nodes without significant lymphangiogenesis and lymphangiectasia in SAH mice.…”
Section: Implications For the Mechanism And Therapeutic Strategies Of...mentioning
confidence: 99%
“…After microvasospasms in the compensation period, platelet aggregation 20 and leukocyte plugging 21 in capillaries cause microcirculatory dysfunction in the decompensation phase. When the microthrombi fill microvessels 22 and impair the glymphatic drainage system, 23 the whole microcirculation collapses without blood flow, and microcirculatory dysfunction moves into an irreversible phase. Recent findings involving neutrophil extracellular traps (NETs) 24 released from neutrophils after SAH might represent important intersections amongst platelet aggregation, microthrombosis, and microglia-mediated inflammation, 25 further supporting the pathophysiological characteristics of the irreversible phase of microcirculation.…”
Section: Intersections In the Pathophysiological Changes Induced By T...mentioning
confidence: 99%
“…Stroke associated with hemorrhage or ischemia is one of the recent research hotspots. Much meaningful work has described the importance of the MIS in cerebral stroke, including subarachnoid hemorrhage ( 99 , 100 ), intracerebral hemorrhage ( 101 ), or ischemic stroke ( 102 , 103 ). In the brain injury studies, meningeal lymphatic drainage is reported to be associated with prognosis ( 104 , 105 ).…”
Section: Meningeal Immune System Response To Central Neural System Di...mentioning
confidence: 99%